Evaluation of the Patients' Expectations and Satisfaction with Physicians in Iranian Public Clinics: A Study Conducted in Kerman - Sareh Balavar; Leila Vali; Seyed Hossein Saberi Anaraki; Yunes Jahani; Rahil GhorbaniNia (Shiraz University of Medical Sciences, 2023)
Background: More satisfied patients in medical care accelerate the progress of treatments and achieve the foremost goal of treatment, which is to improve patients. The aim of this study was to assess the patients' expectations and satisfaction with physicians working in public clinics in Kerman.Methods: This is a cross-sectional study conducted in four clinics under the auspices of Kerman University of Medical Sciences. 385 patients were enrolled in the study using simple random sampling. Britten questionnaire was used to collect the data. The collected data were analyzed through SPSS22 using appropriate tests. The validity of the questionnaire was confirmed using the content method. Cronbach's alpha was calculated for reliability, which was 0.8 for the Reasons of visiting the Doctor Questionnaire and 0.9 for the questionnaire after the examination.Results: The highest expectations of patients (73%) in the reasons for seeing a doctor were related to the diagnosis of the disease, and the lowest expectations were related to the tests and the desire to prescribe (28.6%). Overall satisfaction with the physician was 55.3% among the patients. There was no significant difference between the patients' expectations of the physician with any of the demographic characteristics. Patients' expectations before and after seeing a doctor were not significantly different.Conclusion: Understanding the relationship between the treatment team and the patient means that the decisions made for patients are not dependent on the treating physician and patients' expectations.